A Robust Agar–PAM Hydrogel for Efficient Solar Steam Generation. Issue 10 (7th August 2022) - Yang, Tingting; Mu, Xiaojiang; Zhou, Jianhua; Wang, Pengfei; Chen, Huan; Wang, Xiaoyang; Miao, Lei
Abstract : Freshwater generation by solar distillation is a promising technology to relieve global water scarcity. However, the evaporation of water requires a lot of energy, and the fragile purifier is easily damaged, resulting in low water production in practical applications. Therefore, a material simultaneously possessing low water evaporation enthalpy and strong toughness is desired. Herein, the authors introduced agar into polyacrylamide (AP) to uniquely design hydroxyl group ramparts on the skeleton of hydrogel to uniquely design hydroxyl groups rampart on the skeleton of hydrogel to strengthen robustness of hydrogel and regulate water state, which not only reduces energy demand for evaporation but resists external disturbance. The tensile stress of CNT100 ‐AP1/9 hydrogel reaches the maximum value of 102 kPa while the tensile strain is 467%. Finally, a high evaporation rate of ≈3 kg m −2  h −1 with 86.2% photothermal conversion efficiency is obtained under 1 kW m −2 illumination. The ingenious structure to wear hydroxyl groups coat on the skeleton of PAM hydrogel opens a new avenue for building a new robust and efficient solar thermal desalination system. Abstract : An agar–PAM‐based integrated photothermal conversion hydrogel evaporator with an interconnected pore structure, good robustness, and adjustable internal water state is synthesized by regulating the introduction of agar, thus achieving high evaporation performance and providing an effective strategy for fresh water production.